2021
DOI: 10.3390/pharmaceutics13081155
|View full text |Cite
|
Sign up to set email alerts
|

Morus alba Root Extract Induces the Anagen Phase in the Human Hair Follicle Dermal Papilla Cells

Abstract: Restoring hair follicles by inducing the anagen phase is a promising approach to prevent hair loss. Hair follicle dermal papilla cells (HFDPCs) play a major role in hair growth via the telogen-to-anagen transition. The therapeutic effect of Morus alba activates β-catenin in HFDPCs, thereby inducing the anagen phase. The HFDPCs were treated with M. alba root extract (MARE) to promote hair growth. It contains chlorogenic acid and umbelliferone and is not cytotoxic to HFDPCs at a concentration of 20%. It was demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…AEMA induced the anagen phase by activating the β-catenin in DPCs, enhancing the growth factor secretion. The study showed that AEMA has hair growth-promoting potential [ 95 ]. AEMA increased the expression of proliferative and anti-apoptotic genes in human dermal fibroblasts and promoted the expression of hair-growth-related genes in DPCs.…”
Section: Role Of Phytochemicals In Hair Growthmentioning
confidence: 99%
“…AEMA induced the anagen phase by activating the β-catenin in DPCs, enhancing the growth factor secretion. The study showed that AEMA has hair growth-promoting potential [ 95 ]. AEMA increased the expression of proliferative and anti-apoptotic genes in human dermal fibroblasts and promoted the expression of hair-growth-related genes in DPCs.…”
Section: Role Of Phytochemicals In Hair Growthmentioning
confidence: 99%
“…VEGF is a well-known angiogenesis-promoting growth factor that stimulates hair growth in both mice and humans. An increase in angiogenesis may accelerate anagen transition and hair follicle re-growth [ 10 ]. VEGF transgenic mice display an increased number and size of hair follicles compared to wild-type mice [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of vessels‐like structures was examined and the images were taken by fluorescence microscope BZX710 (KEYENCE). The number of tube formations was counted by a researcher who was blind to the assay condition, as a previous report (Hyun et al, 2021 ; Li et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%